Local area network (LAN) cable tester using arduino - Norimah, Ba'ee (2014)
Tool test local area network (LAN) has become an essential part for all users, especially for students Ethernet network and technical people in the field to test the network. The purpose of this project is to build a network test tool that has an LCD and cheap but the specifications are similar to network test tools are expensive. This system allows the user to test the status of the cable, wire map, show error pin and provide some solution to solve the problem. There are several issues which led to the construction of this project. Among them is a very expensive price for this system is used for the student network and the existing system only uses LEDs to indicate the status of the network cable. It is, students do learn details about cable status. The project is expected to reduce the cost of the University Malaysia Pahang in the purchase of equipment for use in network testing student's computer systems and software engineering (network).